KEEFEKTIFAN BAHAN AJAR MATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Reza Fujianti Syehab; M. Afrilianto; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The use of important teaching materials in the implementation of learning. This research also aims to support mathematics learning to be more interactive and effective and to support student activities in the learning process to improve well. Student learning outcomes also focus on students’ mathematical critical thinking skills. Therefore, the purpose of this study was to determine the effectiveness of mathematic teaching materials on mathematical critical thinking skilss. The research method used in this study is experimental research, namely those obtained from observations, questionnaires and tests. The participants in this research were grade VI students of SMPN 2 Kertasari which consisted of 2 classes. The data analysis used in this research is descriptive analysis. The results of the study show three parts of effectiveness, namely the effectiveness of interaction showing 61% results with a moderately effective category, the effectiveness of understanding which shows 59% results in the moderately effective category and the effectiveness of teaching materials on mathematical critical thinking skills showing 62% results in the moderately effective category. Therefore, the use of mathematics teaching materials on mathematical critical thinking skills is quite good in its delivery and implementation.